Modern political science Anglo-American exchanges since 1880 - Adcock, Robert; Bevir, Mark; Stimson, Shannon C. (Princeton paperbacks, 2007)
Since emerging in the late nineteenth century, political science has undergone a radical shift--from constructing grand narratives of national political development to producing empirical studies of individual political phenomena. What caused this change? Modern Political Science--the first authoritative history of Anglophone political science--argues that the field's transformation shouldn't be mistaken for a case of simple progress and increasing scientific precision. On the contrary, the book shows that political science is deeply historically contingent, driven both by its own inherited ideas and by the wider history in which it has developed. Focusing on the United States and the United Kingdom, and the exchanges between them, Modern Political Science contains contributions from leading political scientists, political theorists, and intellectual historians from both sides of the Atlantic. Together they provide a compelling account of the development of political science, its relation to other disciplines, the problems it currently faces, and possible solutions to these problems. Building on a growing interest in the history of political science, Modern Political Science is necessary reading for anyone who wants to understand how political science got to be what it is today--or what it might look like tomorrow.
Keywords: Political science : History; Political science : United States : History; Political science : Great Britain : History